Rapid Assessment of the Ecological Value of Buaya Lake in Bandar Alai Kari, Kuantan Tengah, Kuantan Singingi Regency, Riau - Rasoel Hamidy; Yusni Ikhwan Siregar (Riau University, 2020)
In Bandar Alai Kari, Kuantan Tengah Sub-district, Kuantan Singingi Regency, Riau, there is a Buaya Lake. According to the history, the Buaya (crocodiles) Lake, used to be a place for river crocodiles to live (an area of approximately 4.5 ha). To obtain data on the value of the lake's conservation status (ecological value), a rapid assessment method is used using the ECELS index. Observations in the field and with the help of drones to observe the components of the ECELS index assessment, the index value is less than 30. From this value it can be concluded that the Bandar Alai Kari crocodile lake is in a very bad conservation status and needs to be restored